Crazy function

Let f f be a function from the set of positive integers to the set of positive integers such that f ( x ) x 2 f(x) \le x^2 for all positive integers x x , and f ( f ( f ( x ) ) f ( f ( y ) ) ) = x y f(f(f(x))f(f(y))) = xy for all positive integers x , y x, y . Find the number of possible values of f ( 30 ) f(30) .

This problem is from the OMO.


The answer is 24.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Zi Song Yeoh
Sep 17, 2014

Throughout this solution, f n ( x ) = f ( f ( . . . f ( x ) ) . . . ) f^{n}(x) = f(f(...f(x))...) , where the function f f is applied n n times.

f f is a function from the set of positive integers to itself such that

( 1 ) (1) f ( x ) x 2 f(x) \le x^2

( 2 ) (2) f ( f 2 ( x ) f 2 ( y ) ) = x y f(f^2(x)f^2(y)) = xy

for all positive integers x , y x, y .

( 1 ) (1) implies f ( 1 ) = 1 f(1) = 1 . Substituing y = 1 y = 1 in ( 2 ) (2) together with f ( 1 ) = 1 f(1) = 1 gives f 3 ( x ) = x f^3(x) = x for all positive integers x x .

Step 1. f f is bijective

If f ( x ) = f ( y ) f(x) = f(y) , then x = f 3 ( x ) = f 3 ( y ) = y x = f^3(x) = f^3(y) = y , so f f is injective. Since f 3 ( x ) = x f^3(x) = x , for every x x there exists y = f 2 ( x ) y = f^2(x) such that f ( y ) = x f(y) = x , so f f is surjective. Thus, f f is bijective.

Step 1 1 implies f 1 = f 2 f^{-1} = f^2 is defined.

Step 2. f ( x ) f ( y ) = f ( x y ) f(x)f(y) = f(xy) and f 1 ( x ) f 1 ( y ) = f 1 ( x y ) f^{-1}(x)f^{-1}(y) = f^{-1}(xy)

By ( 2 ) (2) , f ( f 1 ( x ) f 1 ( y ) ) = f ( f 2 ( x ) f 2 ( y ) ) = x y f(f^{-1}(x)f^{-1}(y)) = f(f^2(x)f^2(y)) = xy . Thus, by applying f 1 f^{-1} to both sides, we get the second identity. Similarly, f ( x ) f ( y ) = f ( f 1 ( f ( x ) f ( y ) ) ) = f ( f 1 ( f ( x ) ) f 1 ( f ( y ) ) ) = f ( x y ) f(x)f(y) = f(f^{-1}(f(x)f(y))) = f(f^{-1}(f(x))f^{-1}(f(y))) = f(xy) .

Step 3. If p p is prime, then f ( p ) f(p) is prime.

Suppose f ( p ) = q r f(p) = qr for some prime p p and some product q r qr with q , r 2 q, r \ge 2 . Then, p = f 1 ( q r ) = f 1 ( q ) f 1 ( r ) p = f^{-1}(qr) = f^{-1}(q)f^{-1}(r) , so p p is the product of two numbers greater than 1 1 , a contradiction. (Since f ( 1 ) = 1 f(1) = 1 and f f is bijective.)

Thus, we can describe all possible f f as a set of ordered triples of primes ( p , q , r ) (p , q, r) , such that f ( p ) = q , f ( q ) = r , f ( r ) = p f(p) = q, f(q) = r, f(r) = p , (WLOG, p < q , r p < q , r ), and with every prime appearing in at most one triple and for all triples p 4 q 2 r p^4 \ge q^2 \ge r . If a prime s s appears in no triples, then f ( s ) = s f(s) = s .

Step 4. All such sets of triples describe a valid f f .

Consider any x = p i x = \prod p_i where each p i p_i is prime. Then, f ( x ) = f ( p i ) = f ( p i ) p i 2 = x 2 f(x) = f(\prod p_i) = \prod f(p_i) \le \prod p_i^2 = x^2 (by ( 1 ) (1) ). So, f f satisfies ( 1 ) (1) . Let y = q i y = \prod q_i where each q i q_i is prime. Then, f ( x ) f ( y ) = f ( p i ) f ( q i ) = f ( x y ) f(x)f(y) = \prod f(p_i) \prod f(q_i) = f(xy) (because p i p_i and q i q_i together are the prime factors of x y xy .) Thus, f f satisfies ( 2 ) (2) .

Now, consider f ( 30 ) = f ( 2 ) f ( 3 ) f ( 5 ) f(30) = f(2)f(3)f(5) . We know that f ( 2 ) { 2 , 3 } f(2) \in \{2, 3\} . If f ( 2 ) = 3 f(2) = 3 , then f ( 3 ) { 5 , 7 } f(3) \in \{5, 7\} . If f ( 3 ) = 5 f(3) = 5 , then f ( 5 ) = 2 f(5) = 2 , giving f ( 30 ) = 30 f(30) = 30 ; if f ( 3 ) = 7 f(3) = 7 , then f ( 5 ) { 5 , 11 , 13 , 17 , 19 , 23 } f(5) \in \{5, 11, 13, 17, 19, 23\} , each of them giving a new value of f ( 30 ) f(30) . Now, we have 7 7 values, all of which are odd except for 30 30 .

If f ( 2 ) = 2 f(2) = 2 , then f ( 3 ) { 3 , 5 , 7 } f(3) \in \{3, 5, 7\} . Either way, f ( 5 ) { 5 , 7 , 11 , 13 , 17 , 19 , 23 } f(5) \in \{5, 7, 11, 13, 17, 19, 23\} . Except

a) f ( 5 ) 5 f(5) \neq 5 if f ( 3 ) = 5 f(3) = 5 .

b) f ( 5 ) 7 f(5) \neq 7 if f ( 3 ) = 7 f(3) = 7 .

c) If f ( 3 ) = 3 f(3) = 3 and f ( 5 ) = 5 f(5) = 5 , then f ( 30 ) = 30 f(30) = 30 , which we already counted.

d) We count f ( 30 ) = 2 5 7 f(30) = 2 \cdot 5 \cdot 7 twice.

That's gives a total of 7 3 4 = 17 7 \cdot 3 - 4 = 17 more values, all of which are even and not 30 30 .

This gives a total of 7 + 17 = 24 7 + 17 = \boxed{24} possible values.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...